Some Issues of the Historical Demography of Artsakh (19th century – the beginning of the 20th century) - Malkhasyan, Mikayel (History and Culture, 2022)
Active demographic processes took place in Artsakh in the 19th century and at the beginning of the 20th century, bringing to various consequences. The purpose of this article is to examine some issues of the historical demography of Artsakh in the mentioned period, which are actively falsified and distorted by Azerbaijani history falsifiers. The article does not aim to present the complete demographic picture of Artsakh in the period under discussion. We have studied the issue of displacement of the Armenian population of Artsakh during the Russo-Persian wars; the issue of the extent of the resettlement of Persian Armenians in Artsakh after the Turkmanchay Treaty (1828); the issue of the proportion of the native Armenian population in Shushi; the connection between monastic land ownership and demography (on the example of Dadivank), and related issues. The research results show that the active migration processes observed in Artsakh since the middle of the 18th century took on new shape during the Russo-Persian wars, in particular, the movements of the Armenian population from the foothills and plains to the mountainous regions. It is important to note that the number of Armenian settlers from Iran in Artsakh was much less than in the territory of the Armenian oblast. Among the issues related to the end of the 19th and the beginning of the 20th century, it is important that the data of the first census of the Russian Empire (1897) and subsequent statistical publications show that Armenians were the majority in Shushi.